The Hydropower Sustainability Assessment Protocol for Use by World Bank Clients : Lessons Learned and Recommendations - Liden, Rikard (World Bank, Washington, DC, 2014)
As a mature technology, hydropower has by far the largest installed capacity of any renewable source of electricity generation. In 1998, in the face of escalating pressure, the World Commission on Dams (WCD) was established by the World Bank and the International Union for Conservation of Nature (IUCN) to review the development effectiveness of large dams and establish a comprehensive set of guidelines for the design, implementation, and operation of dams and their decommissioning. Following the final report of the WCD, the hydropower industry took many steps to operationalize its key recommendations and to improve environmental and social management of hydropower globally. In an effort to improve its performance and provide a consistent approach for assessment, the industry partnered with civil society, policymakers, and financiers around the principles of sustainable hydropower. The output of this process is the multi-stakeholder hydropower sustainability assessment protocol (hereafter referred to as the protocol).The main purpose of this report is to reflect on the applicability of the protocol in developing country contexts, based on the available cases, and offer direction on how it can be used to improve the performance of hydropower projects in World Bank client countries. This report also seeks to clarify the complementarity of the protocol with respect to World Bank policies and procedures and provide input as to the World Bank s role in the governance of the protocol. The lessons and recommendations presented in this report are based on a desk review of previous protocol assessments; consultation with World Bank staff; structured interviews with accredited assessors and developers from previous assessments; as well as direct observations during the pilot assessment of the Trung Son Hydropower Project in Vietnam.